Methodologies to assess the development impact of loan aid: the European experience - Buendía, Luis (Iberoamerican Journal of Development Studies, 2013)
In this paper we analyse the methodologies used by the main European Development Finance Institutions (EDFIs) to assess the development impact of their operations. To do so, we identify the selection criteria of the projects funded by EDFIs using both a literature review −including their own web pages− and on-site interviews. After a short introduction, we start examining the theoretical foundations of the EDFIs’ activities, explaining in the next section what EDFIs are and how they operate. In section 3 we focus on the ex ante methodologies used by the major EDFIs to assess their development impact and in section 4 we present the conclusions of our research. CITE AS: Buendía, L. (2013). Metodologías para la evaluación del impacto en desarrollo de la ayuda reembolsable: la experiencia europea. Iberoamerican Journal of Development Studies, 2 (1): 94-117